JAMUR BASIDIOMYCOTA DI KAWASAN WISATA ALAM PUCOK KRUENG RABA KABUPATEN ACEH BESAR - Nurdin Amin; Eriawati Eriawati; Cut Fira Firyal (Biotik, 2019)
Biodiversity is one of the important components in efforts to manage conservation of resources, this study aims to determine the type of fungus Basidiomycota Division found in Pucok Krueng Raba Nature Tourism, Aceh Besar District. The study was conducted with a roaming method (explorative survey) by directly observing macroscopic fungi found in the tourist attraction area of Pucok Krueng Raba, Aceh Besar Regency, the research location was divided into 3 observation stations. From the results of the study found 12 types of fungi from the Basidiomycota division which is divided into 10 families and most families found in Maramiaceae. The air temperature in the region is 29 C and the humidity is 76%.